Revisiting the Idea That Amyloid-β Peptide Acts as an Agonist for P2X7 - Bibič, Lučka; Stokes, Leanne (Frontiers in Molecular Neuroscience, 2020)
The P2X7 receptor is a cell surface ligand-gated ion channel, activated by its physiological nucleotide agonist ATP and a synthetic analogue (BzATP). However, it has also been suggested that there may be structurally unrelated, non-nucleotide agonists such as the amyloidogenic β peptide. Here we aimed to reassess the effect of amyloid β peptides in various in vitro cell models, namely HEK293 overexpressing human P2X7, the microglial BV-2 cell line, and BV-2 cells lacking P2X7. We measured YO-PRO-1 dye uptake in response to full-length amyloid β peptide (1-42) or the shorter amyloid β peptide (25-35) and there was a concentration-dependent increase in YOPRO-1 dye uptake in HEK-hP2X7 cells. However, these amyloid β peptide-induced increases in YOPRO-1 dye uptake were also identical in non-transfected HEK-293 cells. We could observe small transient increases in [Ca2+]i induced by amyloid β peptides in BV-2 cells, however these were identical in BV-2 cells lacking P2X7. Furthermore, our metabolic viability and LDH release experiments suggest no significant change in viability or cell membrane damage in HEK-hP2X7 cells. In the BV-2 cells we found that high concentrations of amyloid β peptides (1-42) and (25-35) could reduce cell viability by up to 35% but this was also seen in BV-2 cells lacking P2X7. We found no evidence of LDH release by amyloid β peptides. In summary, we found no evidence that amyloid β peptides act as agonists of P2X7 in our in vitro models. Our study raises the possibility that amyloid β peptides simply mimic features of P2X7 activation.